P.234 "Inappropriate" spinal ultrasounds for suspected occult spinal dysraphism in northern Alberta. (November 2021) - Keough, M; Thompson, A; Mehta, V
Abstract : Background: Occult spinal dysraphism (OSD) may be associated with visible cutaneous manifestations. A common non-pathological mimic of a dermal sinus tract is an incidental sacrococcygeal dimple. Choosing Wisely Canada Guidelines recommend these dimples not be imaged. Methods: This study assessed the appropriateness of spinal ultrasounds performed for the investigation of an OSD. We interrogated our local imaging system to analyze spinal ultrasounds being performed in babies less than 6 months of age, from 2017-2018. Results: 429 children had spinal ultrasounds ordered by pediatricians (55%), family doctors (21%), and neonatologists (20%). 183 children (43%) had imaging indications that was deemed "inappropriate". Some of this cohort had further MRI imaging (5/183) or neurosurgical referral (8/183). None of these children underwent neurosurgery. 231 (54%) children had appropriate indications for imaging. Within this cohort MRI imaging (23/231), neurosurgical referral (24/231) and neurosurgical intervention occurred (4/231). All four "surgical children" harboured either a dorsal appendage or a subcutaneous lipoma. We estimated, declining inappropriate scans would save $22, 500 annually. Conclusions: A significant portion of local spinal ultrasound requests for OSD are inappropriate. Collaboration with other sites is ongoing to investigate if the Choosing Wisely guidelines for imaging this patient population are being practiced more efficiently.